The Effectiveness of an Educational Brochure as a Risk Minimization Activity to Communicate Important Rare Adverse Events to Health-Care Professionals. Issue 2 (February 2016) - Bester, Nicolette; Vito-Smith, Michelle; McGarry, Theresa; Riffkin, Michael; Kaehler, Stefan; Pilot, Richard; Bwire, Robert
Abstract Introduction Educational brochures are an important tool for communicating risk to health-care professionals. It is important to evaluate the impact of any risk minimization tool to understand the effectiveness of the strategy. The objective of this study was to assess the effectiveness (i.e., respondents' awareness and understanding of the communication) of a targeted educational brochure distributed to health-care professionals (HCPs) as a risk minimization strategy for the communication of new rare and important adverse events (AEs). Methods A prospective, non-interventional, online survey was performed following distribution of a specifically designed brochure highlighting new and important adverse events to a targeted HCP population, consisting of known users of the target medicine, as represented by a commercial database. Predefined multiple-choice survey questions assessed overall HCP awareness of the brochure and understanding and retention of information in those HCPs who reported receiving the brochure. Results The educational brochure was sent to a total of 565 HCPs; 121 (21.4%) responded to the survey. The majority of respondents (95.0%) had previously prescribed or dispensed the target medicine. In all, 88 (72.7%) respondents said they had received the educational brochure, of whom 95.5% stated they had at least scanned the main points. More participants who had received the brochure (86.4% to 96.6%) answered the five individual survey questions correctly compared with those who did not (51.5% to 97.0%); this was significant for four out of five questions (P ≤ 0.005). Significantly more HCPs who received the brochure achieved the predefined pass rate (at least four of five questions answered correctly) compared with HCPs who did not receive the brochure (93.2% vs 57.6%, respectively;P = 0.000003). Conclusions Distribution of targeted educational brochures may be an effective risk minimization strategy to raise HCP awareness of new rare and important AEs; educational brochures may also be an effective channel for sharing information on how these AEs can be best managed and on the importance and means of reporting AEs. Funding Celgene Pty Ltd, Melbourne, Australia.